Acute posterior multifocal placoid pigment epitheliopathy and sarcoidosis. Issue 1 (January 1988) - Dick, D J; Newman, P K; Richardson, J; Wilkinson, R; Morley, A R
Abstract : We report on a patient with acute posterior multifocal placoid pigment epitheliopathy and sarcoidosis. A review of the literature suggests that sarcoidosis may occur more commonly in this condition than previously suspected.